2009
DOI: 10.1097/icu.0b013e32832f8016
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of age-related macular degeneration

Abstract: First-degree relatives of patients with AMD tend to have a higher risk of AMD. Recognizing an inherent genetic risk of AMD in these patients will improve their management and potentially help prevent blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 159 publications
1
38
0
4
Order By: Relevance
“…23,26,36 -39 Other genes such as complement factor B, C2, C3, SCARB1, and APOE are also implicated in AMD. 40,41 However, due to their low allelic frequencies, the inclusion of these genes alongside both CFH and ARMS2/LOC387715 in this study would not have allowed sufficient power to detect an effect. The prevalence of the different clinical forms of AMD was similar to other observations in Caucasian populations.…”
Section: Discussionmentioning
confidence: 82%
“…23,26,36 -39 Other genes such as complement factor B, C2, C3, SCARB1, and APOE are also implicated in AMD. 40,41 However, due to their low allelic frequencies, the inclusion of these genes alongside both CFH and ARMS2/LOC387715 in this study would not have allowed sufficient power to detect an effect. The prevalence of the different clinical forms of AMD was similar to other observations in Caucasian populations.…”
Section: Discussionmentioning
confidence: 82%
“…AMD is a complex disorder known to result from environmental and genetic factors (Seddon et al, 2011). While an array of genes have been identified as susceptibility factors to the disease (Ting et al, 2009;Yachimski et al, 2009), the mechanism of AMD progression has not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants such as vitamins C, E, and carotenoids, glutathione peroxidase, metallathionein, melanin, SOD, catalase, GSTs, glutathione, and ascorbate occur in high concentrations in the RPE cells [6,7,10] . Several studies have shown that human donor AMD eyes contain higher levels of protein adducts resulting from the oxidative modification of carbohydrates and lipids and higher levels of antioxidant enzymes compared with non-AMD eyes, which indicates that oxidative stress plays an important role in AMD [23,24] . The role of oxidative stress is further strengthened by epidemiological studies demonstrating increased risk with smoking, a potent oxidizing stress, and decreased risk with diets rich in antioxidants such as lutein/zeaxanthin [8] .…”
Section: Discussionmentioning
confidence: 99%
“…CFH dysfunction may lead to excessive inflammation and tissue damage involved in the pathogenesis of AMD [27] . Also, the role of SNPs of many other genes including fibulin 5, SOD, apolipoprotein E, and chemokine receptor 3 have been investigated in AMD pathogenesis [23,24,28] .…”
Section: Discussionmentioning
confidence: 99%